2012
DOI: 10.1002/jcb.23449
|View full text |Cite
|
Sign up to set email alerts
|

Ins and outs of Mycobacterium tuberculosis PPE family in pathogenesis and implications for novel measures against tuberculosis

Abstract: Mycobacterium tuberculosis is the most successful pathogen with multiple mechanisms to subvert host immune response, resulting in insidious disease. A unique Mycobacterium antigen family termed PPE (Pro-Pro-Glu) has long been widely speculated as "molecular mantra" to escape host immunity. Members of this family are characterized by a conserved N terminal and a variable C terminal. This family associated closely with ESAT-6(ESX) secretion system and largely located in cell wall or cell membrane. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…It is closely associated with the ESAT-6 secretion system and largely located in the cell wall or cell membrane; all members of this family are characterized by a conserved N-terminal and a variable C-terminal. The expression of PPE protein is temporally modulated and highly expressed during MTB persistence [124]. One member of the PPE family is Pro-Pro-Glu 38 (PPE38), which inhibits the transcription of genes encoding MHC class I and decreases the number of CD8 + T cells in the spleen, liver and lungs.…”
Section: Other Mechanisms Helping M Tuberculosis To Escape Immunementioning
confidence: 99%
“…It is closely associated with the ESAT-6 secretion system and largely located in the cell wall or cell membrane; all members of this family are characterized by a conserved N-terminal and a variable C-terminal. The expression of PPE protein is temporally modulated and highly expressed during MTB persistence [124]. One member of the PPE family is Pro-Pro-Glu 38 (PPE38), which inhibits the transcription of genes encoding MHC class I and decreases the number of CD8 + T cells in the spleen, liver and lungs.…”
Section: Other Mechanisms Helping M Tuberculosis To Escape Immunementioning
confidence: 99%
“…Many other PE/PPE proteins also induce anti‐inflammatory cytokine signalling (Balaji et al ., ; Basu et al ., ; Nair et al ., ; Bansal et al ., 2010a,b; Beaulieu et al ., ). Comprehensive reviews of how PE/PPE proteins modulate host immune responses can be found elsewhere (Sampson, ; Akhter et al ., ; Deng and Xie, ). Although technical variations in the numerous published studies make it difficult to compare and interpret the results obtained, it is evident that several family members have the capacity to influence host immune responses.…”
Section: Pe/ppe Protein Family and Host Immune Response: A Complex Rementioning
confidence: 99%
“…69 members of PPE multigene antigen family have been found exclusively among mycobacteria [3,4]. PPE family shares a conserved N-terminal around 110 and 180 amino acid residues and a significant variable C-terminal with both sequences and sizes [5].…”
Section: Introductionmentioning
confidence: 99%